THE INFLUENCE OF BRAND TRUST, LIVE PROMO, AND PRICE ON CONSUMER PURCHASING INTEREST IN TIKTOK SHOP IN THE SOUTH SULAWESI REGION - Angreni, Novi; Maszudi, Edi; Adil, Adil (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research aims to examine the impact of Brand Trust, Live Promo, and Price on Consumer Purchasing Interest in TikTok Shop. The study focuses on TikTok Shop users in the South Sulawesi area, with the exact number of respondents not being specified. A total of 200 respondents participated in the study. The research utilized a Likert scale for measurement, and data analysis was conducted using SPSS version 22. The findings of this study reveal that (1) Brand Trust significantly and positively influences consumer purchasing interest in TikTok Shop in the South Sulawesi area, (2) Live Promo has a significant and positive effect on consumer purchasing interest in TikTok Shop in the South Sulawesi area, (3) Price significantly and positively impacts consumer purchasing interest in TikTok Shop in the South Sulawesi area, and (4) Brand Trust, Live Promo, and Price collectively have an effect on consumer purchasing interest in TikTok Shop in the South Sulawesi area. Keywords: Brand Trust; Live Promo; Price; Purchasing Interest